2010
DOI: 10.1007/s11205-010-9769-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of a Portuguese Version of the Subjective Happiness Scale

Abstract: The Subjective Happiness Scale (SHS) constitutes an instrument for assessing subjective happiness. This study aims to present the validation of the SHS in a Portuguese adult population. A large representative sample (1,017 participants), from five different age groups was considered. Configurational invariance of the unidimensional structure of the scale was tested through multi-group confirmatory factorial analysis, and reliability and criterion-validity were investigated. The results support the single facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
17

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 22 publications
6
35
1
17
Order By: Relevance
“…However, a Portuguese study with people aged 25 to 50 years, reported no significant differences according to age [17] although this may be influenced by the limited age range. Regarding gender, women usually report higher scores of QOL [12], but recent studies reported no statistical significant differences [17][18][19], including one with Portuguese population [17]. People with higher levels of education report higher levels of QOL or higher levels of QOL's domains [15; 20] and people living in rural areas describe their QOL more positively than people living in the inner city [21].…”
Section: Introductionmentioning
confidence: 93%
“…However, a Portuguese study with people aged 25 to 50 years, reported no significant differences according to age [17] although this may be influenced by the limited age range. Regarding gender, women usually report higher scores of QOL [12], but recent studies reported no statistical significant differences [17][18][19], including one with Portuguese population [17]. People with higher levels of education report higher levels of QOL or higher levels of QOL's domains [15; 20] and people living in rural areas describe their QOL more positively than people living in the inner city [21].…”
Section: Introductionmentioning
confidence: 93%
“…This tool has presented excellent psychometric properties in several countries 27,28,29,30 . A validation study 26 found the SHS to be reliable, with alpha coefficients varying from 0.80 to 0.94 in 14 different samples (N = 2.732).…”
Section: • the Subjective Happiness Scale (Shs)mentioning
confidence: 99%
“…The SHS is a 4-item test that evaluates happiness from the respondent´s own perspective. The instrument has presented excellent psychometric properties in several countries (Moghnie & Kazarian, 2012;Spagnoli, Caetano, & Silva, 2010;Shimai, Otake, Utsuki, Ikemi, & Lyubomirsky, 2004;Swami, 2008;Swami et al, 2009). In the validation study (Lyubomirsky & Lepper, 1999), the authors found adequate reliability index, with alpha coeffi cients varying from .80 to .94 in 14 different samples (N = 2.732).…”
Section: Instrumentsmentioning
confidence: 99%